2016
DOI: 10.1111/1750-3841.13448
|View full text |Cite
|
Sign up to set email alerts
|

Pea and Broad Bean Pods as a Natural Source of Dietary Fiber: The Impact on Texture and Sensory Properties of Cake

Abstract: Attention has focused on bakery products such as cake which is one of the most common bakery products consumed by people in the world. Legume by-products, pea pods (PPs) (Pisum sativum L.) and broad bean pods (BBPs) (Vicia faba L.) mediterranean (Tunisian), has been studied for its high dietary fiber content (PP: 43.87 g/100 g; BBP: 53.01 g/100 g). Protein content was also a considerable component for both by-products. We investigated the effect of substituted of 5%, 10%, 15%, 20%, 25%, and 30% of PP and BBP f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 34 publications
5
35
3
Order By: Relevance
“…(2016) (6.73 g/100 g) and Mateos‐Aparicio, Redondo‐Cuenca, Villanueva‐Suárez, Zapata‐Revilla, and Tenorio‐Sanz (2010) (10.8 g/100 g). However the protein content obtained in our study was found to be less than the reported value by Belghith‐Fendri et al, 2016) (13.37 g/100 g). Due to the presence of good amount of sugar (fructose, glucose, and sucrose) the PPP was sweet in taste.…”
Section: Resultscontrasting
confidence: 93%
See 2 more Smart Citations
“…(2016) (6.73 g/100 g) and Mateos‐Aparicio, Redondo‐Cuenca, Villanueva‐Suárez, Zapata‐Revilla, and Tenorio‐Sanz (2010) (10.8 g/100 g). However the protein content obtained in our study was found to be less than the reported value by Belghith‐Fendri et al, 2016) (13.37 g/100 g). Due to the presence of good amount of sugar (fructose, glucose, and sucrose) the PPP was sweet in taste.…”
Section: Resultscontrasting
confidence: 93%
“…The values of fiber content were less than the earlier reported values of Fendri et al. (2016); Mateos Aparicio et al (2010) and Belghith‐Fendri et al (2016). The chlorophyll content (1.309 mg/100 g) and ash content of PPP (4.61% ± 0.28%) was found to be less than the reported values of other researchers.…”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…Varieties with small- to medium-size seeds are mostly used for animal feed ( Crépon et al, 2010 ). Faba bean can also be used in the bakery industry ( Belghith-Fendri et al, 2016 ); for example, a combination of faba bean and wheat flour improves the nutritional properties of bread ( Coda et al, 2017 ). In Spain, small faba bean seeds (<12 mm) are currently highly accepted in the industry ( Cubero, 2017 ).…”
Section: Harvest Processing Nutritional Value and Use Of Faba Beanmentioning
confidence: 99%
“…With their gluten-free profile, high protein and fibre content, and low glycemic index, these grain legumes have lately been regarded as valuable alternative ingredients for the production of flours to be used in the development of new food formulations (Vaz Patto et al 2015;Carbas et al 2018). Examples include noodles (Song and Yoo 2017), pastas (Howard et al 2011), biscuits (Sparvoli et al 2016;Dauda et al 2018) and cakes (Belghith-Fendri et al 2016;Shaabani et al 2018). As such, for quality improvement in breeding programs and for the selection of the best genetic material, certain traits must be characterised for genetic diversity within different germplasm collections.…”
Section: Introductionmentioning
confidence: 99%